Reclaiming and Reconstituting our Understanding of “Environment” in Social Work Theory - Mulvale, James (Canadian Social Work Review / Revue canadienne de service social, 2017)
Social work theory has had an inconsistent record in regard to adequately addressing the “environment” in all of its aspects. In the past, social work theory has focused overwhelmingly on the social environment of those whom the profession serves, and has ignored or minimized aspects of clients’ physical and natural environment. In recent decades, however, social work has more adequately theorized the importance of all aspects of environment. The “idealist” and the “structural” approaches to connecting social work and the environment have brought us closer to adequately theorizing the relationship between environmental sustainability and social justice. Social work’s theoretical perspectives on the environment can now extend their scope and usefulness if they draw insights from political economy, and deploy a range of public policy ideas to shape improved social programs and new tax and transfer mechanisms. In these ways, the discipline and profession of social work can make substantial contributions to attaining the linked goals of environmental sustainability and social justice.